Oriented self-assembly of anisotropic layered double hydroxides (LDHs) with 2D-on-3D hierarchical structure - Cao, Jingjing; Feng, Zimou; Liang, Huaxing; Lu, Xinglin; Wang, Wei (Chemical engineering journal (Lausanne, Switzerland : 1996), 2023)
[Display omitted] •A facile-oriented self-assembly for synthesizing 2D-on-3D CoNi-LDHs nanoflowers.•The unique 2D-on-3D structure manifests excellent energy-storage performance.•The formation mechanism was oriented to self-assembly and Ostwald ripening. Layered double hydroxides (LDHs) have been the subject of increasing research due to their unique 2D or 3D structures and promising applications. However, achieving precise control over their morphology and architecture has proven to be a significant challenge. In this work, we present an oriented self-assembly strategy for the synthesis of ultrathin 2D-on-3D CoNi-LDHs nanoflowers (NFs) at ambient temperature. Ex situ and in situ characterization techniques were employed to elucidate the formation process of the 2D-on-3D CoNi-LDHs hierarchical structure. The 2D nanosheets are composed of CoNi(OH)2 seeds that undergo rapid nucleation and growth. Under the influence of oriented attachment and Ostwald ripening, the 2D nanosheets continue to crystallize along the axial and radial directions, resulting in the formation of 2D-on-3D CoNi-LDH NFs. This unique 2D-on-3D LDHs structure possesses an ultrathin thickness of approximately 1.5 nm, nanopores with a diameter of approximately 3.8 nm, and a large surface area of approximately 154 m2/g. These properties manifest excellent energy-storage performance in supercapacitors. Our approach provides important insights into the precise synthesis of LDHs with a 2D-on-3D hierarchical structure. The synthesis of LDHs with well-defined structures is a significant challenge in materials science. Our work contributes to the advancement of this field and has the potential to facilitate the development of new, high-performance energy-storage devices.